1987
DOI: 10.1007/bf00312692
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with the endoscopic application of fibrin tissue adhesive in the upper gastrointestinal tract

Abstract: During a 15-month period, a total of 11 patients underwent endoscopic application of fibrin tissue adhesive in the upper gastrointestinal tract. Our sample consisted of 6 patients with control of bleeding, 4 patients with management of anastomotic leaks, and one very old man undergoing prophylactic sealing of a chronic gastric ulcer with a visible vessel and repeated episodes of bleeding. The method described has proven to be successful in control of bleeding in every case and has resulted in quick cleaning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Endoscopic filling of the fistula with fibrin glue is reported as an effective treatment [17]. Thrombin and fibrinogen provide the surgical seal, and adhesion strength Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic filling of the fistula with fibrin glue is reported as an effective treatment [17]. Thrombin and fibrinogen provide the surgical seal, and adhesion strength Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, with the introduction of different types of biological tissue adhesives and the development of dual and triple lumen catheters in 1984, fibrin glues have been used in the endoscopic treatment of fistulas of the digestive tract [34] . However, only proximal and distal digestive tract fistulas are accessible for endoscopic evaluation and management.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the elevated concentration of the different components present inside the Tissucol P.U., histological studies showed that a soaring proliferation of fibroblasts is present only 4 hours after medication in humans [20]. During the first week the proliferation of newly growing capillary bed is present (as demonstrated in rabbit bone, known to be refractory to regeneration), leading to a wide tissue repairing [19].…”
Section: The Fibrin Glue In Surgery Why?mentioning
confidence: 98%